Propagation of a electromagnetic radiation in the strong magnetic quadrupole and gravitational field - Abishev, M.; Toktarbay, S.; Khassanov, M.; Abylayeva, A. (Recent Contributions to Physics, 2018)
In the work, the nonlinear effect of the magnetic quadrupole field on the propagation of electromagnetic waves in the eikonal approximation of the parametrized post-Maxwell electrodynamics of the vacuum is calculated. Equations of motion for electromagnetic pulses transmitted in a strong magnetic field by two normal modes with mutually orthogonal polarization are constructed. The difference in propagation times of normal waves from the common source of electromagnetic radiation to the receiver is calculated. It is shown that the front and back parts of any hard radiation pulse due to the nonlinear electromagnetic influence of the magnetic quadrupole field turn out to be linearly polarized in mutually perpendicular planes, and the remaining part of the pulse must have elliptical polarization.